Child sexual abuse : whose problem? Reflections from Cleveland - Richardson, Sue; Bacon, Heather (Policy Press, 2018)
Re-issued with a new preface and concluding reflections and recommendations, this book provides an informed understanding of the Cleveland child abuse crisis of 1987 and draws links with current issues in child protection, such as historical and organised abuse.